A Multidimensional Legal Approach to Combat Land Mafia: Regulation, Digital Systems, and Agrarian Legal Education - Ikhsan Lubis; Duma Indah Sari Lubis; Andi Hakim Lubis (JUSTISI, 2026)
This study aims to examine strategies for eradicating land mafia practices through a normative legal approach supported by a digital land administration system and agrarian law education. The method used is a normative legal approach, based on an analysis of primary, secondary, and tertiary legal materials in Indonesia's national land law system. The novelty of this research lies in its multidimensional legal approach, which combines positive legal regulations, digital land governance, and legal education as interconnected pillars. These three elements are analyzed not as separate initiatives, but as complementary efforts in which legal frameworks such as the Basic Agrarian Law (UUPA) serve as the foundation, the digital land system increases transparency and reduces manipulation, and legal education strengthens public legal awareness to prevent land-related crimes. The results of the study show that although each component has its advantages, challenges remain, especially in the implementation of inconsistent legal regulations such as the UUPA. However, if coordinated effectively, these elements can reinforce each other in the national legal system. In conclusion the integrated application of these components can promote a fair, transparent, and socially just land governance structure.